2017
DOI: 10.1016/j.commatsci.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li on the deformation mechanisms of nanocrystalline hexagonal close packed magnesium

Abstract: Addition of solutes such as lithium enhances ductility of hexagonal-close-packed (hcp) Magnesium (Mg). However, the atomistic underpinning of Li addition on individual deformation mechanisms remain unclear and is the focus of the present work. We compared the deformation mechanisms in nanocrystalline (NC) and single crystal simulation systems of pure Mg and Mg-Li hcp alloys. Five deformation modes are observed in the pure NC Mg with randomly oriented grains-one basal {0001} 1120 , one pyramidal type-I {1011} 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The CRSS of non-basal slip system is about a hundred times higher than that of basal slip, and {0001} < 1120 > dominates the slip behavior in coarse grains and a high plastic anisotropy (Barnett et al, 2004;Karewar et al, 2017). It is the reason that, although AZ31B magnesium alloy has more slip systems than FCC structures, it has poor ductility still when forming temperature is in the range of 20-150 • C. According to Von Mises, to achieve a uniform deformation in the material, at least five independent slip systems should be activated.…”
Section: Discussionmentioning
confidence: 99%
“…The CRSS of non-basal slip system is about a hundred times higher than that of basal slip, and {0001} < 1120 > dominates the slip behavior in coarse grains and a high plastic anisotropy (Barnett et al, 2004;Karewar et al, 2017). It is the reason that, although AZ31B magnesium alloy has more slip systems than FCC structures, it has poor ductility still when forming temperature is in the range of 20-150 • C. According to Von Mises, to achieve a uniform deformation in the material, at least five independent slip systems should be activated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the BCC β phase exhibits a total of forty-eight slip systems at room temperature, i.e., twelve (112) [111] type slip systems, twelve (110) [111] type slip systems, and twelve (123) [111] type slip systems [19]. For polycrystalline materials, at least five independent slip systems are needed for the homogenous plastic deformation of materials [20]. As a consequence, the ductility of dual-phase Ti alloys is majorly governed by the HCP α phase, which exhibits limited slip systems.…”
Section: Phase Composition Effects On Deformation Modesmentioning
confidence: 99%
“…Using the metric proposed by Bhatia et al [6], the conclusion of Reddy and Groh suggests that segregated Ca alloying elements increases the grain boundary sliding energy barrier. Within the same idea, Karewar et al [9] investigated numerically the effect of a random distribution of Li alloying elements on the ductility of magnesium-based alloys using empirical potentials. These authors revealed a decrease of the plastic anisotropy by enhancing the activity of the non-basal slip system and tension twinning ሼ101 ത 2ሽ〈101 ത 1〉.…”
Section: Accepted Manuscriptmentioning
confidence: 99%